2016
DOI: 10.1016/j.jnci.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion molecules expression in CLL: Potential impact on clinical and hematological parameters

Abstract: The level of different adhesion molecules expression in CLL is apparently reflected on the potential migratory behavior of the leukemic cells to different organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
3
6
3
Order By: Relevance
“…In contrast, Ibrahim et al showed that CD38 expression is associated with hepatomegaly and aggressive clinical stages (9). Also, the signi cant association between CD38 expression and splenomegaly and intermediate and high-risk disease was reported by some other studies (17,18). In contrast to some reports in the literature, we found that the percentage of CD38 expression has no signi cant correlation with CBC results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, Ibrahim et al showed that CD38 expression is associated with hepatomegaly and aggressive clinical stages (9). Also, the signi cant association between CD38 expression and splenomegaly and intermediate and high-risk disease was reported by some other studies (17,18). In contrast to some reports in the literature, we found that the percentage of CD38 expression has no signi cant correlation with CBC results.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to some reports in the literature, we found that the percentage of CD38 expression has no signi cant correlation with CBC results. Studies have reported that CD38 expression has a positive correlation with WBC and lymphocyte count (18,19) and a negative correlation with Hb concentration and platelet count (9,15,17,19). Although there was not any signi cant correlation between CD38 expression and NLR (r = 0.307, p = 0.073), the higher percentage of this marker was associated with higher NLR.…”
Section: Discussionmentioning
confidence: 93%
“…There was no signi cant association between CD38 expression and each clinical parameter (lymphadenopathy, splenomegaly, Rai staging, modi ed Rai staging, and Binet staging systems). This nding is consistent with that of Abdelgader et al and Kamel et al studies, which reported no signi cant association between CD38 expression and clinical parameters (15,16). In contrast, Ibrahim et al showed that CD38 expression is associated with hepatomegaly and aggressive clinical stages (9).…”
Section: Discussionsupporting
confidence: 91%
“…There was no significant association between CD38 expression and each clinical parameter (lymphadenopathy, splenomegaly, Rai staging, modified Rai staging, and Binet staging systems). This finding is consistent with that of Abdelgader et al and Kamel et al studies, which reported no significant association between CD38 expression and clinical parameters [16,17]. In contrast, Ibrahim et al showed that CD38 expression is associated with hepatomegaly and aggressive clinical stages [9].…”
Section: Discussionsupporting
confidence: 91%